2017
DOI: 10.1007/s00787-017-1002-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum levels of kynurenine metabolites in paediatric patients affected by ADHD

Abstract: This study aims at determining serum levels of tryptophan and other metabolites of the kynurenine pathway in children with attention deficit hyperactivity disorder (ADHD) compared to healthy controls. Such metabolites interact with glutamate receptors in the central nervous system, potentially modulating mechanisms that are pivotal in ADHD and thus potentially representing peripheral biomarkers of the disorder. We measured serum levels of tryptophan and some metabolites of the kynurenine pathway in 102 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…In addition, shorter pregnancy durations and lower birth weights are linked to symptom severities and increased 3-HK and IFN-γ levels in children with ADHD 32 . Moreover, ADHD children with or without comorbidities show significantly reduced AA and KYNA serum levels and increased TRP and KYN levels 67 . In contrast, ADHD is associated with lower concentrations of TRP, KYNA, and 3-HAA in the serum in adults 68 , and mean serum levels of TRP and KYNA and KYNA/KYN ratio are significantly lower in patients with ASD 69 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, shorter pregnancy durations and lower birth weights are linked to symptom severities and increased 3-HK and IFN-γ levels in children with ADHD 32 . Moreover, ADHD children with or without comorbidities show significantly reduced AA and KYNA serum levels and increased TRP and KYN levels 67 . In contrast, ADHD is associated with lower concentrations of TRP, KYNA, and 3-HAA in the serum in adults 68 , and mean serum levels of TRP and KYNA and KYNA/KYN ratio are significantly lower in patients with ASD 69 .…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian study using 133 adult ADHD patients and 133 without found that the ADHD group had lower levels of tryptophan and neuroprotective KA and XA [86]. These data were confirmed by another study testing ADHD children, which exhibited lower KA and XA levels [93]. These researchers, however, recorded higher levels of tryptophan in ADHD subjects [93].…”
Section: Kynurenine Pathwaymentioning
confidence: 70%
“…In fact, many other human studies found in the literature addressing the role of gut microbiota in brain disorders are about the spectrum of behavior disorders, such as Attention-deficit/hyperactivity disorder (Jiang et al, 2018 ); stress-related disorders (Ghavami et al, 2018 ); and major depressive disorder (Lin et al, 2017 ; Chen et al, 2018 ). The approaches used to investigate possible connections between gut and brain include (i) gut microbial manipulation with antibiotics (Schmidt et al, 2018 ); (ii) pre/probiotics administration (Tillisch et al, 2013 ; Chambers et al, 2015 ); (iii) fecal microbiota transplantation (Jalanka et al, 2018 ); (iv) post-mortem examination of the brain (Zhan et al, 2016 ); (v) metabolomics/metagenomics analysis of biological samples (e.g., feces, mucosal biopsy) (Evangelisti et al, 2017 ; Labus et al, 2017 ).…”
Section: Pathological Conditions Of the Microbiota-gut-brain Axis: Fomentioning
confidence: 99%